2016
DOI: 10.1002/hed.24564
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing sialocele or salivary fistula formation postparotidectomy

Abstract: Sialocele/salivary fistula is common postparotidectomy and is more likely with inferior and middle superficial parotidectomy. © 2016 Wiley Periodicals, Inc. Head Neck 39: 387-391, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 16 publications
1
20
1
2
Order By: Relevance
“…One study evaluated the incidence rate of sialocele [ 53 ] and two studies reported the incidence of salivary fistula[ 44 , 47 ], however, no statistical difference was reported between AFND and RFND parotidectomies. In a study performed by Britt et al,[ 64 ] they reported that no association has been observed between the volume of tissue removed during parotidectomy and the incidence rate of sialocele or salivary fistula and this was in line with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…One study evaluated the incidence rate of sialocele [ 53 ] and two studies reported the incidence of salivary fistula[ 44 , 47 ], however, no statistical difference was reported between AFND and RFND parotidectomies. In a study performed by Britt et al,[ 64 ] they reported that no association has been observed between the volume of tissue removed during parotidectomy and the incidence rate of sialocele or salivary fistula and this was in line with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Sialocele was reported in 102 studies 10,14,15,17,23,25,33–36,38,39,41–44,46,48,50,51,56–62,64,66,67,69,70,72–77,79–85,87–90,92,95,96,98,100–103,106–108,110–116,118–121,125,128,135–138,141,144,146,147,150–169 reporting on 13,760 patients (Table I and Fig. 2C).…”
Section: Resultsmentioning
confidence: 97%
“…Als eine Alternative zur Einlage einer Drainage nach einer Parotidektomie wird die Anlage eines postoperativen Kompressionsverbandes beschrieben. Eine kontrollierte Anwendung wurde jedoch bis jetzt in validen Studien nicht geprüft [13,14].…”
Section: Evidenzlage Zur Wertigkeit Einer Wunddrainage Bei Speicheldrunclassified
“…Somit ist eine signifikant höhere Probandenzahl notwendig, um den Effekt der Drainage auf das Risiko der postoperativen Nachblutung zu evaluieren (s. Kapitel Biometrie). Die Prävalenz einer Sialozele (Speichelzyste) lag in unserem Patientengut bei 10-15 % [8,13,18]. Diese Zahlen decken sich ebenfalls mit den Angaben aus der internationalen Literatur 10-39 % [8].…”
Section: Evidenzlage Zur Wertigkeit Einer Wunddrainage Bei Speicheldrunclassified